Implementasi Algoritma Multiplicative Congruential Random Number Generator Pada Aplikasi Seleksi Mojang Jajaka - Tito Sugiharto; Lutfi Slamet Riyadi; Heru Budianto; Dede Irawan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Mojang Jajaka (MOKA) is one of icons of tourism ambassadors who come from most districts/cities in West Java. The selection of tourism ambassadors in Kuningan was organized by the Department of Youth, Sports and Tourism (DISPORAPAR) of Kuningan, and the Mojang Jajaka Association of Kuningan. One of the series of activities carried out is participant registration and written test selection. Currently the registration process and the written test selection are still carried out conventionally by collecting hardcopy files and writing tests using a sheet of paper. This is considered less effective and efficient because using paper often causes problems, namely tucked, damaged, and easily lost. In the written test activities, cheating often occurs when filling out answers. This study aims to apply the Multiplicative Congruential Random Number Generator Algorithm in randomizing the questions on the MOKA selection test. The selection process begins with participants registering on the application. Then the participant logs in and after that the admin sees the participant data and then verifies the participant data. After that the admin will do question management, where the admin will input 30 questions. Then the participants will carry out the exam process. The Multiplicative Congruential Random Number Generator algorithm will work to randomize the questions from 30 questions and 25 questions will be issued. This application is made using the Java programming language, PHP, Javascript and MySQL database. This study uses the RUP (Rational Unified Process) methodology which consists of 4 stages, namely Inception, Elaboration, Construction, and Transition. This study results a MOKA Selection Application that can simplify the registration process and written test selection for both participants and the Mojang Jajaka selection committee, Kuningan.